A dark-light transition triggers expression of the floral promoter CrFTL1 and downregulates CONSTANS-like genes in a short-day plant Chenopodium rubrum - Drabešová, Jana; Cháb, David; Kolař, Jan; Haškovcová, Kateřina; Štorchová, Helena (Journal of experimental botany, 2014)
The proper timing of flowering is essential for the adaptation of plant species to their ever-changing environments. The central position in a complex regulatory network is occupied by the protein FT, which acts as a florigen. We found that light, following a permissive period of darkness, was essential to induce the floral promoter CrFTL1 and to initiate flowering in seedlings of the short-day plant Chenopodium rubrum L. We also identified two novel CONSTANS-like genes in C. rubrum and observed their rhythmic diurnal and circadian expressions. Strong rhythmicity of expression suggested that the two genes might have been involved in the regulation of photoperiod-dependent processes, despite their inability to complement co mutation in A. thaliana. The CrCOL1 and CrCOL2 genes were downregulated by dark-light transition, regardless of the length of a preceding dark period. The same treatment activated the floral promoter CrFTL1. Light therefore affected CrCOL and CrFTL1 in an opposite manner. Both CrCOL genes and CrFTL1 displayed expression patterns unique among short-day plants. Chenopodium rubrum, the subject of classical physiological studies in the past, is emerging as a useful model for the investigation of flowering at the molecular level.
Keywords: Florigen; testy genetické komplementace; gene expression; short-day plant.; sekvence aminokyselin; FLOWERING LOCUS T-like; Plant Proteins; Flowers; flowering; Genetic Complementation Test; polymerázová řetězová reakce s reverzní transkripcí; Amino Acid Sequence; rostlinné proteiny; Reverse Transcriptase Polymerase Chain Reaction; light sensitivity; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Sequence Alignment; Chenopodium rubrum; CONSTANS-like; Chenopodium; Arabidopsis; promotorové oblasti (genetika); Promoter Regions, Genetic; Photoperiod; semenáček; Seedlings; florigen; sekvenční seřazení; květy; fotoperioda